2021
DOI: 10.1186/s40168-021-01102-0
|View full text |Cite
|
Sign up to set email alerts
|

Candidate probiotic Lactiplantibacillus plantarum HNU082 rapidly and convergently evolves within human, mice, and zebrafish gut but differentially influences the resident microbiome

Abstract: Background Improving probiotic engraftment in the human gut requires a thorough understanding of the in vivo adaptive strategies of probiotics in diverse contexts. However, for most probiotic strains, these in vivo genetic processes are still poorly characterized. Here, we investigated the effects of gut selection pressures from human, mice, and zebrafish on the genetic stability of a candidate probiotic Lactiplantibacillus plantarum HNU082 (Lp082) as well as its ecological and evolutionary imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 47 publications
5
27
0
Order By: Relevance
“…It suggested that there were strong antagonistic relationships between probiotics and indigenous gut microbes, which were more intense in mice. This is consistent with the results of the previous studies 22 . However, correlation analysis revealed that the number and magnitude of local adaptive SNVs were greatly related to the host environment, and which probiotic strain(s) have been supplemented.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…It suggested that there were strong antagonistic relationships between probiotics and indigenous gut microbes, which were more intense in mice. This is consistent with the results of the previous studies 22 . However, correlation analysis revealed that the number and magnitude of local adaptive SNVs were greatly related to the host environment, and which probiotic strain(s) have been supplemented.…”
Section: Discussionsupporting
confidence: 94%
“…To mitigate the potential effect of confounding factors, such as individuality in the gut microbiome, in our analyses, six probiotic studies were focused, including Bifidobacterium longum AH1206 ( B. longum AH1206) 7 , Supherb Bio-25 19 , L. rhamnosus GG 20 , Probio-Fit 21 , L. plantarum HNU082 22 and Lactobacillus casei Zhang ( L. casei Zhang) where host participants had paired/repeated microbiome measurements before and after the probiotic intervention. The correlation pattern between nSNVs and the beta diversity of gut microbiota was highly specific to what probiotic strains had been consumed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, four genes belong to the phosphotransferases system (PTS), a highly conserved bacterial phosphotransferase cascade whose components modulate many cellular functions in response to carbohydrate availability (Deutscher et al, 2006) and which has already been observed to be over-expressed or mutated in other mouse gut colonization experiments (Barreto et al, 2020; Marco et al, 2009; Zhang et al, 2013). This is in line with a recent study showing that L. plantarum convergently evolves across vertebrate animal hosts (i.e., human, mouse, zebrafish) by acquiring mutations primarily modulating carbohydrate utilization and acid tolerance (Huang et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…LBTs face many challenges to survival in the luminal environment, both from the host (e.g., peristalsis, innate and adaptive immunity) and other native microorganisms (e.g., competition, niche availability) ( Walker and Owen, 1990 ). Probiotic strains not adapted to the luminal environment cannot easily compete with microbes that have adapted to their specific luminal niche over thousands of generations ( Huang et al, 2021 ). This phenomenon is apparent in most patients who have received fecal microbiota transplant, where the individual’s native microorganisms return and largely, or completely, displace the transplanted microbes ( Li et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%